Autoimmune Encephalitis in Postpartum Psychosis - Bergink, Veerle; Armangue, Thaís; Titulaer, Maarten J; Markx, Sander; Dalmau, Josep; Kushner, Steven A (American Journal of Psychiatry, 2015)
Objective:Significant immunological alterations have been observed in women with first-onset affective psychosis during the postpartum period. Recent studies have highlighted the possibility that a subset of patients with first-onset severe psychiatric episodes might suffer from undiagnosed autoimmune encephalitis. Therefore, the authors performed a three-step immunohistochemistry-based screening for CNS autoantibodies in a large cohort of patients with postpartum psychosis and matched postpartum comparison subjects.Method:Ninety-six consecutive patients with postpartum psychosis and 64 healthy postpartum women were included. Screening for antibodies in patient serum was performed using immunohistochemistry. Samples showing any staining were further examined by immunocytochemistry using live hippocampal neurons and cell-based assays to test for anti-N-methyl-d-aspartate (NMDA) receptor antibodies. Cell-based assays for all other known CNS antigens were performed in those samples with immunocytochemistry labeling but negative for NMDA receptor antibodies.Results:Four patients (4%) with neuropil labeling suggestive for extracellular antigen reactivity were identified. Serum samples from all four patients showed clear extracellular labeling of live hippocampal neurons. Two women had the specific staining pattern characteristic for anti-NMDA receptor antibody positivity, which was confirmed by cell-based assays. Neither patient with anti-NMDA receptor antibody positivity had evidence of an ovarian teratoma. The other two patients tested negative by cell-based assays for all known CNS antigens. None of the matched postpartum comparison subjects had confirmed neuronal surface antibodies. The two patients with anti-NMDA receptor antibodies both showed extrapyramidal symptoms following initiation of treatment with low-dose haloperidol.Conclusions:In patients with acute psychosis during the postpartum period, systematic screening for anti-NMDA receptor autoantibodies should be considered. The acute onset of severe atypical psychiatric symptoms in young female patients should raise the index of suspicion for anti-NMDA receptor encephalitis, particularly in the setting of neurological symptoms, including extrapyramidal side effects of antipsychotic treatment.